2013
DOI: 10.1080/09585192.2013.777678
|View full text |Cite
|
Sign up to set email alerts
|

Injury-related absenteeism and job satisfaction: insights from Greek and UK data

Abstract: Most of the literature on absenteeism suggest that absence from work is a complex issue influenced by multiple causes, both of personal and of organizational nature. Job satisfaction has also been identified as one of the factors affecting an employee's motivation to work attendance. There is no universal agreement concerning the relationship between absenteeism and job satisfaction. Some research have found no correlation between these two variables, whereas other studies indicate a weak relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
2
9
1
Order By: Relevance
“…In addition, job satisfaction is positively associated with work-related characteristics such as administration control, teaching competence and organizational culture ( Ma & MacMillan, 1999 ). Conversely, employees’ job satisfaction is inversely associated with general ( Hanebuth, 2008 ) and injury-related absenteeism ( Drakopoulos & Grimani, 2013 ), intention to leave the workplace ( MacIntosh & Doherty, 2010 ; Tschopp, Grote, & Gerber, 2014 ), counterproductive interpersonal and organizational behaviors ( Mount, Ilies, & Johnson, 2006 ), job-related stress ( Boudreaux, Mandry, & Brantley, 1997 ), psychological distress ( Moen, Kelly, & Lam, 2013 ) and biological markers of ill-health (such as higher levels of inflammatory cytokines and other lymphocytes; Amati et al, 2010 ). Such negative effects on the teaching professions are crucial since, for instance, job related stress is negatively related with students’ academic achievement ( Banerjee & Lamb, 2016 ; Kalyva, 2013 ).…”
mentioning
confidence: 99%
“…In addition, job satisfaction is positively associated with work-related characteristics such as administration control, teaching competence and organizational culture ( Ma & MacMillan, 1999 ). Conversely, employees’ job satisfaction is inversely associated with general ( Hanebuth, 2008 ) and injury-related absenteeism ( Drakopoulos & Grimani, 2013 ), intention to leave the workplace ( MacIntosh & Doherty, 2010 ; Tschopp, Grote, & Gerber, 2014 ), counterproductive interpersonal and organizational behaviors ( Mount, Ilies, & Johnson, 2006 ), job-related stress ( Boudreaux, Mandry, & Brantley, 1997 ), psychological distress ( Moen, Kelly, & Lam, 2013 ) and biological markers of ill-health (such as higher levels of inflammatory cytokines and other lymphocytes; Amati et al, 2010 ). Such negative effects on the teaching professions are crucial since, for instance, job related stress is negatively related with students’ academic achievement ( Banerjee & Lamb, 2016 ; Kalyva, 2013 ).…”
mentioning
confidence: 99%
“…Congruent with the above studies, Drakopoulos and Grimani [25], [26] who previously conducted a similar research to market laborers, reported that there is a weak negative relationship of job satisfaction and absenteeism. They predicated the two variables might have a stronger relation under particular condition.…”
Section: Negative Direct Influence Of Teacher Job Satisfaction On Absenteeismmentioning
confidence: 82%
“…Job satisfaction research was also deemed to be important for analysing and predicting many key economic variables such as: labour turnover, labour productivity, pay differentials, workers' absenteeism, quits, the role of gender and the degree of unionism in the labour market (e.g. Borjas, 1979;Clark, 1997;Clark, 2001;Hamermesh, 2001;Shields and Price, 2002;Böckerman and Ilmakunnas, 2008;Card, Mas, Moretti and Saez, 2012;Drakopoulos and Grimani, 2013). Finally and considering the recent boom of the related field of happiness research, job satisfaction is viewed as an important predictor of overall well-being (Clark and Oswald, 1996;Sousa-Poza and Sousa-Poza, 2000; Bonsang and Van Soest, 2012).…”
Section: Introductionmentioning
confidence: 99%